2021
DOI: 10.1016/j.celrep.2021.109633
|View full text |Cite
|
Sign up to set email alerts
|

Not4 and Not5 modulate translation elongation by Rps7A ubiquitination, Rli1 moonlighting, and condensates that exclude eIF5A

Abstract: Not4 and Not5 modulate translation elongation by Rps7A ubiquitination, Rli1 moonlighting, and condensates that exclude eIF5A Graphical abstract Highlights d Not subunits of the Ccr4-Not complex form dynamic condensates excluding eIF5A d In notD cells, ribosome dwelling occupancies change according to codon optimality d Ribosome dwelling inversely changes upon eIF5A depletion and Not deletion d Rli1 moonlighting and Rps7A ubiquitination contribute to Not regulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(80 citation statements)
references
References 77 publications
7
72
1
Order By: Relevance
“…In a recent study we showed that the dynamics of translation elongation were greatly affected in the absence of Not4 and Not5 in S.cerevisiae and we proposed that this was due to defective tethering of translating ribosomes to ribonucleoprotein (RNP) condensates, in particular ribosomes paused at non-optimal codons (17). This model predicts that ribosomes paused at non-optimal codons should be enriched in the insoluble mRNA condensates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study we showed that the dynamics of translation elongation were greatly affected in the absence of Not4 and Not5 in S.cerevisiae and we proposed that this was due to defective tethering of translating ribosomes to ribonucleoprotein (RNP) condensates, in particular ribosomes paused at non-optimal codons (17). This model predicts that ribosomes paused at non-optimal codons should be enriched in the insoluble mRNA condensates.…”
Section: Resultsmentioning
confidence: 99%
“…For this latter category the reads for the total RNA pool were less different between the first and second halves of the CDS than for the first category that showed a pattern more similar to that seen for all mRNAs. (17) showed instead a mild inverse correlation with 5'P-RDO changes upon Not5 depletion (Figure S3A). This suggests that in not5D cells limiting amounts of Not1 have a dominant impact on RDOs.…”
Section: Metagene Profiles Of Decay Intermediates Distinguish Mrnas I...mentioning
confidence: 98%
See 2 more Smart Citations
“…An important target for general translation coordination is eS7, that in yeast is monoubiquitinated by the E3 ligase Not4 1 2 9 , a component of the Ccr4-Not complex and master regulator of gene expression 26 . eS7 ubiquitination by Not4 occurs constitutively after canonical translation initiation and it was demonstrated to be required for mRNA homeostasis by serving as a prerequisite of Ccr4-Not's role in degradation of non-optimal mRNAs 1,27 . Monoubiquitination of eS7 is also responsible for translational regulation under ER stress condition 28 .…”
Section: Introductionmentioning
confidence: 99%